Reducing postoperative blood product usage and costs in cardiothoracic surgery: the implementation of a multispecialty perioperative care model incorporating a haemostasis checklist - Krishnaswamy Sundararajan; Peter Hibbert; Christopher Daniel Smith; Adrian De Luca (BMJ Open Quality)
Transfusion of blood products following cardiothoracic surgery represents a significant proportion of national blood product usage, has significant cost implications and is associated with increased 30-day mortality. Following identification of an increase in blood product use, we implemented a healthcare improvement initiative using a perioperative care model and establishment of a new multispecialty cardiothoracic surgery taskforce to further define and tackle the problem. The initiative incorporated a bundle of preoperative identification of high-risk patients, an intraoperative haemostasis checklist, a programme of unit education focussing on bleeding postbypass and use of thromboelastography and introduction of postoperative protocols for identification and escalation of bleeding. Following intervention, a 60% reduction in blood product use within the first 12 hours of cardiopulmonary bypass was observed. Red cell, cryoprecipitate and fresh frozen plasma usage were particularly reduced with 57%, 47% and 72% reductions, respectively, following intervention and similar results were maintained on repeat audit 1-year postintervention, with on average 84 fewer blood products used per 100 patients. This resulted in an estimated cost saving of AU$36 928 per 100 patients. This quality initiative was successful in overcoming traditional silos of care and describes how quality improvement methodology utilising a multispecialty and multidisciplinary approach can be applied to solve complex issues in the perioperative period. Here, we demonstrate a reproducible and sustainable model for reducing blood product use in the cardiothoracic perioperative population.